The effect of different stemperature to the yolk egg shrinkage of silver pompano (Jurnal Intek Akuakultur, 2018)
This research was done on March 2 to 5, 2018 in Desa Pengujan, Bintan Bay II, Bintan Regency. The purpose of this research was to knew the best temperature treatment for development of silver pompano larvae. This research were used Completely Randomized Design (CRD) there were, A (28Â°C), B (30Â°C), C (32Â°C) and D (34Â°C) with 3 replications in each treatment. The results showed that A treatment (32Â°C) had the best yolk volume shrinkage was   84.432.467,5 Âµm3 and the best of egg yolk absorption rate was 4.690.692,6 Âµm3/jam.